Kajian Estetik Teknik Kenteng Tempat Sampah Malioboro - Ifan Rohimanto; Yeffry Handoko Putra (Universitas Komputer Indonesia, 2020)
Malioboro Street in Special Region of Yogyakarta, Indonesia is a tourist area. Both sidewalks on the street facilitated with garden chairs, ornamental plants, ornamental statues, ready to drink tap water, and trash cans. Product aesthetic of Malioboro trash cans is important to be studied since the product will be placed in public facility. Research on trash cans in Malioboro area was conducted to see the content of product aesthetic of the trash can. The analysis method uses the aesthetic theory of Dr. Dharsono, M.Sn (Sony Kartika), which consists of color, shape, texture and proportion.. The results showed the color and natural texture obtained from the aluminum, terrazzo, and sand/Merapi mountain ash. The shape consists of blocks/boxes and tubes with aluminum lids using traditional forging techniques namely kenteng, balanced proportions. Malioboro trash can has product aesthetic value that supports Malioboro tourist area.